Pengaruh Model Pembelajaran TPS Berbasis Pembelajaran Diferensiasi Terhadap Kemampuan Berpikir Tingkat Tinggi Siswa Pada Materi Klasifikasi Makhluk Hidup - Adinda Givinia Rintang; Herry Sumampouw; Mariana Rengkuan (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to discuss the influence of the Think Pair Share (TPS) learning model based on differentiation learning on students' high-level thinking abilities in the material of classification of living creatures at SMP N 4 Dumoga. This research design uses an experiment with a Posttest-Only Control Group Design research design. The research was carried out in class VII with a total of 50 students divided into two groups, namely VII A as the experimental class and class VIIB as the control class. Test high-level thinking skills in the form of analysis, evaluation, and creation questions. The results of hypothesis testing using the t-test obtained tcount = 4.306 > ttable = 2.010 at α = 0.05, which means H0 is rejected and H1 is accepted. The conclusion is that there is a significant influence of the Think Pair and Share (TPS) learning model based on Differentiated Learning on Higher Level Thinking Abilities. Students think at a higher level at SMP N 4 Dumoga.